(untitled) (International Journal of Scientific Trends, 2025)
This article explores the metaphorical conceptualization of the concept “labor” in the English language. Through cognitive linguistic analysis, the study examines how labor is represented metaphorically, revealing underlying cultural values and social attitudes. The paper discusses common metaphors related to labor, such as labor as a journey, labor as a commodity, and labor as a force or energy, highlighting their role in shaping our understanding of work and effort.